Variasi Sistem Sapaan di Instagram - Arumi, Sihindun; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar (Universitas Batanghari Jambi, 2023)
This qualitative research found the type of Instagram greeting and the factors that influence the selection of greetings using data from greeting words in Instagram users' captions from accounts that appeared randomly on the researcher's home page. The methods used are observation, documentation, and content analysis, with researchers using a print screen or munch screen features on computers or mobile phones to document data. The study has identified around 106 greetings in 9 different types, with the greeting to mention loyal customers having the highest number and the kinship greeting being the second. Many bussiness, health, parenting, and daily activities accounts choose kinship greetings to foster closeness or familiarity with their potential targets. This study shows that Instagram is a potential social media to influence customer decisions with information about their business. While there are still opportunities for more specific research, this study contributes to understanding the variety of greetings on Instagram in general.